(3GdQYGjI GdUMjI hGdJCejf GdUMjs - (3JTGQdR(B, (3ajdjHSs ((3GdEScfOQjI(B:s (3GdecJH GdYQHj GdMOjK(B,s, 2012)
(3GbJUGOjGJ GdUMI(B- (3cjajI JOGNd GdCShGb Hjf GdQYGjI GdUMjI hGdJCejf GdUMj(B- (3GdJMhd ef GdQYGjI GdWHjI Gdi GdQYGjI GdUMjI(B- (3GdWdH Ydi GdQYGjI GdUMjI(B- (3OQGSGJ JWHjbjI ddWdH YGi GdQYGjI GdWHjI(B-(3GdWHjH(B- (3GdCWHGA aj GdeMjW GdShbj(B- (3GdeSJTai cehQO ddQYGjI GdWHjI(B- (3GdeSJTajGJ aj GdeMjW GdShbj(B- (3GdWdH Ydi GdJCejf GdUMj(B- (3GdJCejf GdUMj aj GdeMjW GdShbj(B- (3GdJCejf GdUMj GdMchej(B- (3HQGeL CNQi MchejI ddQYGjI GdUMjI(B- (3GdeeGQSGJ GdWHjI GdQOjFI(B- (3GdJfXjeGJ aj bWGY GdQYGjI GdUMjI GdCeQjcjI(B- (3ebGQfGJ OhdjI dfXe GdQYGjI GdUMjI(B- (3JSGDdGJ hGLGHGJ deNWWj GdSjGSGJ GdUMjIs
Keywords: (3EbJUGOs; (3GdJCejf GdUMjs; (3GdQYGjI GdUMjIs